Peutz-Jeghers polyp: A Retrospective Study on Twelve Cases Received at the Department of Pathology, Bangabandhu Sheikh Mujib Medical University - Choudhury, Tamanna; Enam, Suraiya; Begum, Ferdousy; Taufiq, Md.; Kamal, Mohammed (Bangabandhu Sheikh Mujib Medical University Journal, 2012)
Background: Peutz Jegher syndrome is a rare inherited condition characterized mainly by gastrointestinal hamartomatous polyposis and mucocutaneous pigmentation. The polyps are mostly found in the small bowel and less frequently in the stomach and large gut. Objectives: This study was done to observe the clinical and pathological features of Peutz Jegher polyps. Methods: A retrospective study was carried out in the Department of Pathology, Bangabandhu Sheikh Mujib Medical University (BSMMU) during the five and a half year period from 1st January 2006 to 30th June 2011. From the records the cases which were diagnosed as Peutz Jeghers polyps were sorted out, clinical data was compiled and slides were reviewed. Results: During this period 12 cases were diagnosed as Peutz Jeghers polyp. Most of these (n=58.33%) occurred in the second decade of life and majority (n=9) were located in the large gut including sigmoid colon and rectum. Both sessile as well as pedunculated types were seen. All had characteristic histologic features of Peutz Jeghers polyps and in only one case there was a mild dysplastic change in the glandular lining epithelium. Conclusion: Close monitoring of the patients with peutz Jeghers polyp can reduce the morbidity of this condition. DOI: http://dx.doi.org/10.3329/bsmmuj.v5i1.10994 BSMMU J 2012; 5(1):12-17